Bronchodilatory, antitussive and anti‐inflammatory effect of morin in the setting of experimentally induced allergic asthma. (10th June 2016) - Franova, Sona; Kazimierova, Ivana; Pappova, Lenka; Joskova, Marta; Plank, Lukas; Sutovska, Martina
Abstract: Objective: Using an experimental model of allergic asthma, we evaluated the anti‐asthmatic potential of polyphenol flavonol derivate morin after either acute or long‐term treatment of male OVA‐sensitised guinea pigs. Methods: The following methods were used in experiments: the in‐vitro tracheal smooth muscle contraction induced by histamine; the changes in specific airway resistance (sRaw) to histamine and the sensitivity of a chemically induced cough reflex both via an in‐vivo method; the serum and BALF concentrations' analysis of the inflammatory cytokines interleukin IL‐4, IL‐5, IL‐13; and lung tissue infiltration by eosinophils and mastocytes. Key findings: Our data show that acute morin (30 mg/kg) and chronic 21‐day morin (30 mg/kg/day) administration had a comparable antitussive efficiency with opioid antitussive codeine. Acute morin bronchodilatory activity defined by in‐vivo sRaw decline did not reach SABA salbutamol effect. However, bronchodilatory efficiency of morin after long‐term administration was by 34% higher as effect of LABA salmeterol. The 21‐day morin treatment of OVA‐sensitised guinea pigs reduced the serum, BALF levels of IL‐4 and IL‐13, lung tissue eosinophil and mastocyte infiltration comparable with corticosteroid budesonide. Conclusions: In summary, morin represents very rational target for additional studies as potential substance for control as well as prevention of asthma inflammation and symptoms.